Early-childhood cytomegalovirus infection and children's neurocognitive development. (11th December 2020) - Lee, Samantha M; Mitchell, Ruth; Knight, Julia A; Mazzulli, Tony; Relton, Caroline; Khodayari Moez, Elham; Hung, Rayjean J
Abstract: Background: Despite a clear association seen in congenitally infected children, the effect of postnatal cytomegalovirus (CMV) infection during early childhood on cognitive development has not yet been determined. Methods: CMV-infection status was obtained based on serological measurements when children were 7 years old. Using population-based longitudinal data, we employed multivariate Poisson regression with a robust variance estimator to characterize the relationship between childhood CMV infection and adverse neurocognitive outcomes in children. Suboptimal neurocognitive outcomes were compared between CMV-positive and CMV-negative children using various cognitive assessments from 8 to 15 years of age. Children were evaluated on the cognitive domains of language, reading, memory and general intelligence, with a suboptimal score being >2 standard deviations lower than the mean score. Approximate Bayes factor (ABF) analysis was used to determine the level of evidence for the observed associations. Results: With adjustment for potential confounders, we observed that early-childhood CMV infection was associated with suboptimal total intelligence quotient (IQ) at 8 years of age [incidence-rate ratio (IRR) = 2.50, 95% confidence interval (CI) 1.35–4.62, ABF = 0.08], but not with suboptimal total IQ at 15 years of age (IRR = 0.97, 95% CI 0.43–2.19, ABF = 1.68). Suboptimal attentional control at 8 years (IRR = 1.74, 95% CI 1.13–2.68, ABF = 0.18) and reading comprehension at 9 years (IRR = 1.93, 95% CI 1.12–3.33, ABF = 0.24) were also associated with CMV infection. ABF analysis provided strong evidence for the association between CMV infection and total IQ at 8 years, and only anecdotal evidence for attentional control at 8 years and reading comprehension at 9 years. All other cognitive measures assessed were not associated with CMV infection. Conclusion: In this large-scale prospective cohort, we observed some evidence for adverse neurocognitive effects of postnatal CMV infection on general intelligence during early childhood, although not with lasting effect. If confirmed, these results could support the implementation of preventative measures to combat postnatal CMV infection.